2020
DOI: 10.1186/s12944-020-01212-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of Chinese high-fat dietary habits on lipid metabolism: mechanisms and health implications

Abstract: Background: The traditional Chinese diet blends lard with vegetable oil, keeping the fatty acid balance intake ratio of saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids at nearly 1:1:1. However, the effects of a mixture of lard and vegetable oil on lipid metabolism have never been researched. In the present study, by simulating Chinese high-fat dietary habits, we explored the effects of a mixture of lard and vegetable oil on lipid metabolism. Methods: We randomly assigned 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Because saturated fatty acids (SFAs) increase low-density lipoprotein cholesterol (LDL-C), the consumption of lard has significantly reduced in recent years. However, the majority of earlier lard-related studies utilized a high-fat diet [13][14][15], which is very dissimilar from the diet of Asian nations, including China. While moderate lard consumption was shown in human intervention trials to increase LDL-C in comparison to plant oils such as soybean oil, olive oil, and palm olein [16,17], in most individuals, the increase in LDL-C is not due to an increase in the levels of small dense LDL particles, but rather, larger LDL particles, which are much less strongly associated with CVD risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because saturated fatty acids (SFAs) increase low-density lipoprotein cholesterol (LDL-C), the consumption of lard has significantly reduced in recent years. However, the majority of earlier lard-related studies utilized a high-fat diet [13][14][15], which is very dissimilar from the diet of Asian nations, including China. While moderate lard consumption was shown in human intervention trials to increase LDL-C in comparison to plant oils such as soybean oil, olive oil, and palm olein [16,17], in most individuals, the increase in LDL-C is not due to an increase in the levels of small dense LDL particles, but rather, larger LDL particles, which are much less strongly associated with CVD risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the content of SA may be affected by species factors ( 29 ). MA is a straight-chain SFAs with 14 carbon atoms and no carbon–carbon double bond, which was originally found in the seeds of nutmeg ( 30 , 31 ). MA is also widely found in animal fats and vegetable oils, including sperm, whale oil, coconut oil, and dairy products ( 32 , 33 ).…”
Section: Effect Of Different Fas On Semen Qualitymentioning
confidence: 99%
“…Some studies even reported a fat energy content of 22% in 1992, and 32.9% in 2012 18 both in China, while a 27% fat energy in west India 19 . In our previous study, we mixed lard with vegetable oil to make SFA: MUFA: PUFA close to 1:1:1, we have found that lard blended with soybean oil has anti-obesity effects under 25% fat energy by decreasing adipogenesis and lipogenesis while increasing the hydrolysis of triglycerides in adipose tissues 20 , but the effects disappeared under 35% fat energy 21 . In the present study, we aimed to investigate whether the anti-obesity effect of balanced fatty acid diet extended to sun ower oil under 30% fat energy, and explore its effects on liver lipids metabolism and serum hormones.…”
Section: Introductionmentioning
confidence: 99%